Metonymy Processing in Chinese: A Linguistic Context-Sensitive Eye-Tracking Preliminary Study - Chen, Xianglan; Ren, Hulin; Yan, XiaoYing (Frontiers in Psychology, 2022)
Current cognitively-oriented research on metaphor proposes that understanding metaphorical expressions is a process of building embodied simulations, which are constrained by past and present bodily experiences (Gibbs, 2006ab). However, it has also been shown that metaphor processing is also constrained by the linguistic context (e.g., Martin 2006 and the references therein) but, to our knowledge, there is no comparable work in the domain of metonymy. As an initial attempt to fill this gap, the present study uses eye-tracking experimentation to explore this aspect of Chinese metonymy processing. It complements previous work by Chen at al. (2019) on how the length of preceding linguistic context influences metonymic processing by focusing on: (1) the contextual information of both the preceding target words; (2) the immediate spillover after the target words; and (3) whether the logical relationship between the preceding contextual information and the target word is strong or weak (a 2×2 between-subject experiment with target words of literal/metonymy and logic of strong/weak). Results show that readers take longer to arrive at a literal interpretation than at a metonymic one when the preceding information is in a weak logic relationship with target words, although this disparity can disappear when the logic is strong. Another finding is that both the preceding and the spillover contextual information contribute to metonymy processing when the spillover information does more to the metonymy than it does to the literal meaning. This study further complements cognitive and pragmatic approaches to metonymy, which are centered on its conceptual nature and its role in interpretation, by drawing attention to how the components of sentences contribute to the metonymic processing of target words. Based on an experiment, a contextual model of Chinese metonymy processing is proposed.